2019
DOI: 10.1111/bioe.12661
|View full text |Cite
|
Sign up to set email alerts
|

Against the family veto in organ procurement: Why the wishes of the dead should prevail when the living and the deceased disagree on organ donation

Abstract: The wishes of registered organ donors are regularly set aside when family members object to donation. This genuine overruling of the wishes of the deceased raises difficult ethical questions. A successful argument for providing the family with a veto must (a) provide reason to disregard the wishes of the dead, and (b) establish why the family should be allowed to decide. One branch of justification seeks to reconcile the family veto with important ideas about respecting property rights, preserving autonomy, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 6 publications
0
7
0
Order By: Relevance
“…Interestingly, we found that the expression of P53 protein and the numbers of apoptotic cells were higher in U2OS cell line than that in Saos2 cell line following treatment with BAY 1816032 and BUB1 gene knockdown. The expression of P53 protein can induce cell apoptosis in osteosarcoma 22,23 . A previous study confirmed that the P53 protein was not present in Saos2 cells 24 but was found in U2OS cells 25 .…”
Section: Discussionmentioning
confidence: 77%
“…Interestingly, we found that the expression of P53 protein and the numbers of apoptotic cells were higher in U2OS cell line than that in Saos2 cell line following treatment with BAY 1816032 and BUB1 gene knockdown. The expression of P53 protein can induce cell apoptosis in osteosarcoma 22,23 . A previous study confirmed that the P53 protein was not present in Saos2 cells 24 but was found in U2OS cells 25 .…”
Section: Discussionmentioning
confidence: 77%
“…1 The role played by the family in organ procurement decision-making may be more consequential than the model of consent (5). To help increase organ donation rates and respect individual autonomy, scholars have proposed to prevent families from overruling their loved one's intention to donate (6,7). In 2006, the USA amended the Uniform Anatomical Gift Act to restrict the family's authority to veto the deceased's first-person authorization.…”
Section: Introductionmentioning
confidence: 99%
“…Some authors have also questioned the ethical permissibility of the family veto, but the few available studies indicate that the public support for the family veto is limited (Albertsen, 2020; Downie et al, 2008). Albertsen (2020) emphasizes that there are no arguments that could justify the family veto and disregard the deceased’s wishes. The Romanian society’s attitude toward this concept represents a new research direction that deserves to be pursued.…”
Section: Resultsmentioning
confidence: 99%